Influence of farm management on the dynamics of Salmonella enterica serovar Infantis shedding and antibiotic resistance during the growing period of broiler chickens - Montoro-Dasí, Laura; Villagrá, Arantxa; Vega, Santiago; Marín, Clara (Wiley Online Library, 2021)
Background: Salmonella enterica serovar Infantis is a zoonotic pathogen isolated in broilers causing great economic losses in the European poultry sector. It is demonstrated that an investment in management measures at farm level could directly affect the control of food chain microorganisms. The aim of this study was to investigate the development of S. Infantis antimicrobial resistance (AMR) patterns during the growing period, according to flock density and ventilation management, without antibiotic administration. Methods: The experiment was performed in two identical poultry houses, evaluating commercial and optimal farm conditions. At 24 h of rearing, 20% of the animals were orally infected with a S. Infantis strain susceptible to all the antibiotics tested. To study Salmonella shedding, faeces samples from each experimental group were taken weekly and analysed as per ISO/TS 6579–2:2017. Antibiotic susceptibility was assessed according to Decision 2013/653. Results: Salmonella shedding showed that the lowest counts were observed in the first week post-infection and highest at slaughter day for both groups. Moreover, 100% of the isolates were multi-resistant. Conclusion: The acquisition of AMR by S. Infantis starts at the onset of the production cycle and is maintained until the end, demonstrating the importance of transmission of AMR in zoonotic bacteria at farm level.